Service Marketing in Online Shopping Platform: Psychological and Behavioral Dimensions - Wang, Yong; Qi, Manci; Parsons, Liz; Tsai, Fu-Sheng (Frontiers in Psychology, 2021)
This conceptual analysis critically discusses how service marketing is workable for online shopping platforms and how important service-related and influenced factors played their roles the aforementioned issue. The concepts of service, service marketing, and related factors were re-visited, or at least reflected, in the new context of online platforms. Mostly, we framed the essence and importance of those discussed factors from the psychological and behavioral angles. Implications for theory, practices, and policy-making were offered seriously.